An investigation of the roles furan versus thiophene π-bridges play in donor–π-acceptor porphyrin based DSSCs. Issue 18 (26th April 2018) - Cariello, Michele; Abdalhadi, Saifaldeen M.; Yadav, Pankaj; Decoppet, Jean-David; Zakeeruddin, Shaik M.; Grätzel, Michael; Hagfeldt, Anders; Cooke, Graeme
Abstract : We show that furan, rather than thiophene, gives rise to higher power conversion efficiencies for this class of porphyrin derivative. Abstract : Dye-sensitized solar cells (DSSCs) continue to attract interest due to their lower cost production compared to silicon based solar cells and their improving power conversion efficiencies. Porphyrin-based sensitizers have become an important sub-class due to their strong absorption characteristics in the visible region, convenient modulation of properties through synthetic manipulation and class-leading power conversion efficiencies. In this article, we report the synthesis and characterization of two porphyrin-based dyes and their application as sensitizers in DSSCs. A thiophene and a furan moiety have been incorporated into the push–pull architecture as a π-bridge, allowing the systematic investigation of how these moieties influence the physical properties of the dyes and the performance of their resulting DSSCs. A significant difference in PCEs has been observed, with the furan containing dye (PorF, PCE = 4.5%) being more efficient than the thiophene-based analogue (PorT, PCE = 3.6%) in conjunction with the iodide/triiodide redox electrolyte.